Stop Rubber Bullets. The use of kinetic energy projectiles and torture in the Spanish State - Franquesa Griso, Anaïs; Guillot Campillo, Carles; Quintana Porras, Ester; Pérez Sales, Pau; Urango Montilla, Irene; Vigara Mas, Serlinda (Torture Journal, 2024)
Rubber bullets are projectiles whose use is potentially lethal. Between 1976 and 2017, they have caused at least 23 deaths and dozens of injuries in Spain, many of them serious, with loss of sight being the main cause. In the period 2000 - 2020 alone, more than 40 people have been affected. However, the data available do not reflect, in quantitative terms, the reality of the problem which, far from the figures for other contexts, shows qualitative impacts, both individual and collective. This article reviews the trajectory of the last twenty years, emphasising those key aspects that have made a difference in the process towards the prohibition of this weapon in different territories of the state, as well as evaluating the psychosocial impacts that its use has caused.